Rodríguez-Consuegra, Francisco A., “Russell, Gödel and Logicism”, in: Czermak (Hg.) 1993 [Zbl. 0836.00022], 233–242 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Majer, Ulrich, “Different Forms of Finitism”, in: Czermak (Hg.) 1993 [Zbl 0836.00022], 185–194 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete [Zbl. 0838.03003])

Franchella, Miriam, “Griss’ Contribution to Intuitionism”, in: Czermak (Hg.) 1993 [Zbl 0836.00022], 119–126 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Degen, J.W., “Two Formal Vindications of Logicism”, in: Czermak (Hg.) 1993 [Zbl. 0836.00022], 243–250 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Rheinwald, Rosemarie, „Die Achilles-Paradoxie in der modernen Diskussion“, in: Czermak (Hg.) 1993 [Zbl 0836.00022], 383–392 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Grattan-Guinness, Ivor, “Structure-Similarity: Between Mathematics and Philosophy”, in: Czermak (Hg.) 1993 [Zbl 0836.00022], 317–333 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Code, Murray, “Understanding, Intuition, and the Philosophy of Mathematics”, in: Czermak (Hg.) 1993 [Zbl 0836.00022], 335–342 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Detlefsen, Michael, “The Kantian Character of Hilbert’s Formalism”, in: Czermak (Hg.) 1993 [Zbl 0836.00022], 195–205 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Wolenski, Jan, “Analyticity, Decidability and Incompleteness”, in: Czermak (Hg.) 1993 [Zbl 0836.00022], 379–382 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

De Caro, Mario, “Galileo’s Mathematical Platonism”, in: Czermak (Hg.) 1993 [Zbl 0836.00022], 13–22 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Franchella, Miriam, “L.E.J. Brouwer: Toward Intuitionistic Logic”, Historia Mathematica 22 (1995), 304–322 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Puhl, Klaus (Hg.), Philosophy of Mathematics. Proceedings of the 15th International Witt-genstein-Symposium, 16–23 August 1992, Kirchberg am Wechsel, Austria, Part 2, Hölder-Pichler-Tempsky: Wien 1993 (= Schriftenreihe der Wittgenstein-Gesellschaft; 20/II) [Zbl. 836.00023] - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Bolzano, Bernard, Miscellanea mathematica 10, hg. v. Bob van Rootselar/Anna van der Lugt, Frommann-Holzboog: Stuttgart-Bad Cannstatt 1995 (Bernard Bolzano-Gesamtausgabe; II.B.6.2) - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Tichy, Matthias, “Mathematics and Philosophy in Wittgenstein: Dissolution of a Reflectional Relationship”, in: Puhl (Hg.) 1993 [Zbl 0836.00023], 144–150 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Segre, Michael, “Peano's Axioms in Their Historical Context”, Archive for History of Exact Sciences 48 (1994), 201–342 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Hintikka, Jaakko, “The Original Sinn of Wittgenstein’s Philosophy of Mathematics”, in: Puhl (Hg.) 1993 [Zbl. 836.00023], 24–51 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Mixed-Mode BIST Using Embedded Processors - Hellebrand, Sybille; Wunderlich, Hans-Joachim; Hertwig, Andre (IEEE International Test Conference (ITC'96))

Casati, Roberto/Smith, Barry/White, Graham (Hgg.), Philosophy of the Cognitive Sciences. Proceedings of the 16th International Wittgenstein-Symposium, 15–22 August 1993, Kirchberg am Wechsel, Austria, Hölder-Pichler-Tempsky: Wien 1994 (= Schriftenreihe der Wittgenstein-Gesellschaft; 21) - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Haugeland, John, “Remarks on Machines and Rule-Following”, in: Casati/Smith/ White (Hgg.) 1994 [Zbl 0849.00032], 127–138 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Bealer, George, “Toward a New Theory of Content”, in: Casati/Smith/White (Hgg.) 1994 [Zbl 0849.00032], 179–191 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Hintikka, Jaakko, “Why Parallel Processing?”, in: Casati/Smith/White (Hg.) 1994 [Zbl 0849.00032], 265–272 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Echeverria, Javier, “Observations, Problems and Conjectures in Number Theory — The History of the Prime Number Theorem”, in: J. Echeverria et al. (eds.), The Space of Mathematics, Walter de Gruyter: Berlin 1992 [ Zbl 0839.00019], 230–252 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Grattan-Guinness, Ivor, “Structure-similarity as a Cornerstone of the Philosophy of Mathematics”, in: J. Echeverria et al. (eds.), The Space of Mathematics, Walter de Gruyter: Berlin 1992 [ Zbl 0839.00019], 91–111 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Otte, Michael, “Constructivism and Objects in Mathematical Theory”, in: J. Echeverria et al. (eds.), The Space of Mathematics, Walter de Gruyter: Berlin 1992 [Zbl. 0839.00019], 296–313 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Torretti, Roberto, “Mathematical Structures and Physical Necessity”, in: J. Echeverria et al. (eds.), The Space of Mathematics, Walter de Gruyter: Berlin 1992 [Zbl 0839.00019], 132–140 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Breger, Herbert, “Tacit Knowledge in Mathematical Theory”, in: J. Echeverria et al. (eds.), The Space of Mathematics, Walter de Gruyter: Berlin 1992 [Zbl 0839.00019], 79–90 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

MacLane, Saunders, “The Protean Character of Mathematics”, in: J. Echeverria et al. (eds.), The Space of Mathematics, Walter de Gruyter: Berlin 1992 [ Zbl 0839.00019], 1–13 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Howson, Colin, “Mathematics in Philosophy”, in: J. Echeverria et al. (eds.), The Space of Mathematics, Walter de Gruyter: Berlin 1992 [Zbl 0839.00019], 192–201 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Heinzmann, Gerhard, Zwischen Objektkonstruktion und Strukturanalyse. Zur Philosophie der Mathematik bei Jules Poincaré, Vandenhoeck & Ruprecht: Göttingen 1995 (= Studien zur Wissenschafts-, Sozial- und Bildungsgeschichte der Mathematik; 10) - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Resnik, Michael D., “Applying Mathematics and the Indispensability Argument”, in: J. Echeverria et al. (eds.), The Space of Mathematics, Walter de Gruyter: Berlin 1992 [Zbl 0839.00019], 115–131 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Mosterín, Jesús, “Theories and the Flow of Information”, in: J. Echeverria et al. (eds.), The Space of Mathematics, Walter de Gruyter: Berlin 1992 [Zbl 0839.00019], 367–378 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Dathe, Uwe, „Gottlob Frege und Rudolf Eucken - Gesprächspartner in der Herausbildungsphase der modernen Logik“, History and Philosophy of Logic 16 (1995), 245–255 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Knobloch, Eberhard/Pieper, Herbert/Pulte, Helmut, „...das Wesen der reinen Mathematik verherrlichen“, Mathematische Semesterberichte 42 (1995), 99–132 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Quesada, Daniel, “State of Affairs and the Evolution of Carnap’s Semantics”, Logique & Analyse Nouv. Sér. 36 (1993), 149–157 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Woleński, Jan, “Mathematical Logic in Poland 1900–1939: People, Circles, Institutions, Ideas”, Modern Logic 5 (1995), 363–405 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Murawski, Roman, “Contributions of Polish Logicians to Decidability Theory”, Modern Logic 6 (1996), 37–66 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Jean Piaget zur Einführung - Scharlau, Ingrid

Wissenserwerb und Raumreferenz. Ein sprachpsychologischer Zugang zur mentalen Repräsentation - Buhl, Heike M.

Erwerbssituation, mentale Repräsentation und sprachliche Lokalisationen - Blickpunktinformation als Bestandteil der Raumrepräsentation - Buhl, Heike M. (Sprache und Kognition)
Explored the question of point of view as a part of the mental representation of space. Human Ss: 80 normal German adults (university students) (Exp 1). 48 normal German adults (university students) (Exp 2). Ss participated in 2 separate experiments in which spatial expressions were taken to indicate the point of view in mental representation and in which one object was localized within a route direction context. Results were discussed as to whether working memory load offers an explanation for the availability of viewpoint oriented information that allows for changes in mentally represented point of views.

"Verschleiertes Geschlecht". Zum subversiven Potential des Fetisch bei Judith Butler und Marjorie Garber - Öhlschläger, Claudia; Deuber-Mankowsky, Astrid; Konnertz, Ursula (Die Philosophin. Forum für feministische Theorie und Philosophie. Heft 13/April 1996: Fetisch. Frau)

Forumsbeitrag: Bericht über das Münchner Graduiertenkolleg Geschlechterdifferenz und Literatur - Öhlschläger, Claudia (Der Deutschunterricht 1/1996: Differenzen - diesseits und jenseits von Geschlechterfixierungen (Hg.) Eva Kublitz-Kramer und Eva Neuland)

Sagen können, wie es hier ist, werd ich ja nie. Bildlektüren des Unbeschreiblichen in Rainer Maria Rilkes Briefen aus Spanien (1912/13) - Öhlschläger, Claudia (Hofmannsthal- Jahrbuch 4)

Unsägliche Lust des Schauens. Die Konstruktion der Geschlechter im voyeuristischen Text - Öhlschläger, Claudia

Lamellar lyomesophases under shear as studied by deuterium nuclear magnetic resonance - Lukaschek, M.; Müller, S.; Hasennindl, A.; Schmidt, Claudia; Grabowski, D. A. (Colloid & Polymer Science)
Keywords: Materials Chemistry; Colloid and Surface Chemistry; Polymers and Plastics; Physical and Theoretical Chemistry

Solid State NMR Investigation of C1-Deuterated Poly(di-n-hexylsilylene) - Müller, Christian; Schmidt, Claudia; Frey, Holger (Macromolecules)
Keywords: Materials Chemistry; Inorganic Chemistry; Polymers and Plastics; Organic Chemistry

Texte – Konstitution, Verarbeitung, Typik

A Review of A History of Women Philosophers. Hrsg. von Mary Ellen Waithe. New York u.a.: Springer 1987-1995: Review - Hagengruber, Ruth Edith (Sudhoffs Archiv)

Sicherheitserziehung - ein Thema für den Arbeitslehreunterricht. - Bigga, Regine (ARBEIT UND TECHNIK in der Schule)

Interaktiver Produktdatenaustausch mit EDIFACT - Aisch, H.; Joosten, M.; Müller, Wolfgang; Buijs, F.

Integrating a Constraint Solver into a Real-Time Animation Environment - Griebel, P.; Lehrenfeld, Georg; Müller, Wolfgang; Tahedl, C.; Uhr, H. (Proceedings of the 1996 IEEE Symposium on Visual Languages)
Investigates the integration of an interactive constraint solver into an existing 2D real-time animation environment in order to achieve a better observability, traceability and stability of the individual graphical objects. We present two approaches for assigning constraints to the objects. The first approach assigns constraints to the objects when they are created, keeping them stable during their entire life-time. The second approach dynamically changes constraints before the computation of each frame. The investigation is based on our practical experience with the complete visual programming language Pictorial Janus and the parallel constraint solver Parcon.
Keywords: Animation; Layout; Computer languages; Visualization; Observability; Stability; Runtime; Costs; Graphics; Hardware